2019
DOI: 10.21831/jpv.v9i3.27719
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between vocational high schools and world of work: A case study at SMK Taman Karya Madya Tamansiswa

Abstract: The purpose of this study was to find out: the school strategy, procedure, forms, and evaluation to cooperate with the world of work. The type of research is qualitative with a case study approach. The subjects in this study were the head of the department, the chairman of the special job fairs, the vice-principal of public relations, the vice-principal of curriculum, the head of competence skills, and industry that were in cooperation with the school. The methods of collecting the data were in-depth interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Pendekatan penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif, yaitu mengambarkan tingkat kemampuan guru Sekolah Menengah Kejuruan dalam mengajar bidang keahlian baru yang didapat setelah mengikuti Program Keahlian Ganda (Baitullah & Wagiran, 2019). Dimana tujuan dari pendekatan deskriptif ini adalah untuk menyajikan gambaran lengkap mengenai kemampuan guru terhadap pelaksanaan pembelajaran di kelas.…”
Section: Metodeunclassified
“…Pendekatan penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif, yaitu mengambarkan tingkat kemampuan guru Sekolah Menengah Kejuruan dalam mengajar bidang keahlian baru yang didapat setelah mengikuti Program Keahlian Ganda (Baitullah & Wagiran, 2019). Dimana tujuan dari pendekatan deskriptif ini adalah untuk menyajikan gambaran lengkap mengenai kemampuan guru terhadap pelaksanaan pembelajaran di kelas.…”
Section: Metodeunclassified
“…Demikian juga hasil penelitian Suryanto, (2012) menyimpulkan bahwa (1) pelaksanaan pembelajaran praktek produktif di SMK Negeri I Kalijambe Sragen program keahlian Tata Buasana dilaksanakan dari kelas X sampai XII menganut model PSG (2) kerja sama yang dilaksanakan dengan perusahaan berupa praktek kerja industri (Prakerin) dan perekrutan tenaga kerja; (3) hasil praktik siswa berbentuk nilai dan produk barang/pakaian, penilaian dilakukan oleh guru selama proses kegiatan dan melihat hasil praktik siswa. Hasil kajian Baitullah & Wagiran (2019) antara memberikan informasi yang relatif sama berkenaan dengan bentuk kerja sama dalam pelatihan peningkatan keterampilan di bidang ilmu pengetahuan dan teknologi, pertukaran informasi, sinkronisasi dan pengembangan kurikulum, implementasi magang, pelaksanaan uji kompetensi dan sertifikasi, kunjungan industri, kerja industri praktek, bursa kerja khusus, dan rekrutmen.…”
Section: Hasil Dan Pembahasanunclassified
“…First, strengthening the relationship of SMK with business and industry in the 21st century. Second, pushing local advantages into global advantages (Baitullah and Wagiran, 2019). Furthermore, Wibowo (2016) suggested that schools through the BKK should cooperate with the industrial world so that the industry is willing to become a place for graduates to work.…”
Section: Program Data Required By Graduate Usersmentioning
confidence: 99%
“…In line with the findings of the analysis of the needs of students/graduates, managers, and users and based on an important indicator of the success of vocational education is the aspect of relevance, so that Vocational High Schools are required to be able to produce graduates who are competitive and ready to take part in the global era. Career counselling services are important, but do not have a strategic place in schools (Abubakar, Sitti Rahmaniar, 2011;Abdullah-Al-Mamun, 2012;Bridgeland & Bruce, 2014;Baitullah, Muh. Juandi Arif, and Wagiran, 2019).…”
Section: Model Integrated Solutionmentioning
confidence: 99%